Laboratory Diagnosis of Dengue Virus Infection - Tri Wibawa (Tropical Medicine Journal, 2012)
ABSTRACTDengue virus (DENV) infection was reported by more than 100 countries in the world. DENV was estimated infects 2.5 billion people living at tropical and subtropical countries annually.  Laboratory diagnosis of DENV infection is important for the best clinical management of the patients. There are many tools and methods have been developed and dedicated to serve accurate diagnostic of DENV infection. In hitherto, laboratory diagnosis of DENV infection may be done by several methods, i.e. serology, viral culture, and viral genome-based detection. However, there is no convincing diagnosis procedures that easy to be performed and user friendly. This review will address the principle and characteristic of the laboratory diagnostic procedures that is available at this moment.